PENGARUH INTELLECTUAL CAPITAL DAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN - jumriati Safira; Biana Adha Inapty (Jurnal Riset Akuntansi, 2024)
This study aims to examine the influence of intellectuall capital and good corporate governance on the company's financial performance in mining companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period. The approach employed in this study using a sample of 145 companies was purposeful sampling. Return on Asset (ROA) is the dependent variable that is measured using a panel data regression model. Intellectuall capital, institutional ownership, audit committee, independent board of commissioners, and management ownership were the study's independent factors. The test results demonstrate that a companny's financial success is positively impacted by its intellectuall capital. In the meantime, for mining companies listed on the Indonesia Stock Exchange for the 2018–2022 period, good corporate governance, as measured by institutional ownership, the number of audit committees, an independent board of commissioners, and managerial ownership, has no bearing on the company's financial performance. The research's conclusions benefit businesses and investors in real ways. This research can be used as a consideration in applying the variables in this study to help improve company performance and is also expected to help investors in making the right decisions in investing.